“Deep Listening” in Buddhist Studies: Teaching and Learning during a Pandemic - Frances Garrett; Sophie Chase (Religions, 2021)
Co-authored between a professor and student, this essay discusses how an experiential learning assignment of “deep listening” was integrated into an online course on histories of Buddhist meditation. Paired with a group art project, the work provided not only an opportunity to practice critical communication skills, but also a sense of connection and community, which is especially important during the conditions of pandemic isolation. The course design relied on pedagogical principles specifically aimed at supporting student well-being, such as trauma-informed teaching. We reflect on how grounding course design in inclusive, anti-oppressive and care-focused principles may enable new outcomes in teaching and learning beyond this pandemic year.